Assessment and Prioritization of Contractor Internal Schedule Delay Risks in Phnom Penh High-Rise Building Projects Using Relative Importance Index Method - Res Haitin; I Putu Artama Wiguna (Newinera Publisher, 2026)
The rapid expansion of high-rise building projects in Phnom Penh has been accompanied by persistent schedule delays that significantly impact project performance. While external factors are often emphasized, contractor internal risks represent controllable factors requiring systematic assessment and prioritization. This study aims to identify and prioritize contractor internal delay risk factors in high-rise building projects in Phnom Penh through quantitative analysis of expert perceptions. A mixed-methods approach was employed, combining qualitative data collection through structured questionnaires with quantitative analysis using the Relative Importance Index (RII). Data were collected from 97 construction professionals involved in high-rise projects (exceeding 10 floors) in Phnom Penh during 2020–2025. Seventeen internal risk factors were assessed across probability (RII-P) and impact (RII-I) dimensions. Analysis identified three critical risks with Risk Scores ≥ 0.60: Poor Planning and Scheduling (RII-P: 0.81, RII-I: 0.83, Risk Score: 0.68), Cash Flow Problems (RII-P: 0.76, RII-I: 0.83, Risk Score: 0.64), and Ineffective Monitoring and Control (RII-P: 0.79, RII-I: 0.79, Risk Score: 0.62). Fourteen additional risks were classified as Medium Priority (Risk Scores: 0.46–0.56). Managerial and financial factors dominate internal delay risks in Phnom Penh's high-rise construction, suggesting contractors should prioritize planning systems, financial management, and monitoring controls to improve schedule performance. These findings have implications for similar developing construction markets, particularly in Indonesia.